2016
DOI: 10.1111/eth.12521
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Parasitism Risk and Host Infection Status Affect Patch Use in Foraging Wild Mice

Abstract: Foraging host individuals can defend against fecal–orally transmitted parasites by avoiding feces‐contaminated patches, which has been widely documented among ungulates. However, it remains unclear whether smaller‐sized hosts (e.g., mice), with their high metabolism and constant needs for energy acquisition, can afford the same behavioral strategy. In this study, we used laboratory and field experiments to test whether feces‐contaminated patches are avoided by the Taiwan field mice Apodemus semotus. In the lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Another study on this A. semotus population has demonstrated that ivermectin‐treated adults preferred food patches without conspecific feces (Hou et al. ). Although the same study did not find the mice to discriminate between food patches with low‐FEC vs. high‐FEC feces, it still suggests that A. semotus can use conspecific feces as cues to make decisions on patch choice.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Another study on this A. semotus population has demonstrated that ivermectin‐treated adults preferred food patches without conspecific feces (Hou et al. ). Although the same study did not find the mice to discriminate between food patches with low‐FEC vs. high‐FEC feces, it still suggests that A. semotus can use conspecific feces as cues to make decisions on patch choice.…”
Section: Discussionmentioning
confidence: 90%
“…To confirm ivermectin efficacy and quantify environmental infection risks, we performed fecal egg count (FEC, the number of strongyle nematode eggs per gram of feces) following Hou et al. ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The site was on a river terrace isolated from other forested areas by rivers, paved roads, and orchards. The physical isolation of the site from other suitable habitats helped to ensure a high capture rate (c. 99%; Hou et al, 2016) that is critical to parentage analysis. A 9-ha grid comprised of 332 trapping stations (15 m between adjacent stations; Figure S1) was set up to cover the entire site.…”
Section: Study Site and Mouse Trappingmentioning
confidence: 99%
“…Similarly, parasite avoidance should be most pronounced when infection risk is aggregated and detectable. Hosts can flee from biting vectors (Hart 1994) and some skin‐penetrating infective stages (Karvonen et al , Taylor et al ), but for passively ingested (or otherwise undetectable) infectious stages, avoidance depends on associated cues, such as odor (Kavaliers and Colwell , Poirotte et al ), a carcass (Capinera et al , Turner et al ) or feces (Cooper et al 2000, Hou et al ). Human disgust towards feces is nearly universal and likely protects against disease (Curtis and Biran , Curtis ); however, we know relatively little about the extent to which wild animals detect and react to such indirect cues about parasitism risk, in part because it can be difficult to measure how transmission risk varies across a landscape.…”
Section: Introductionmentioning
confidence: 99%